Efektivitas Media Pembelajaran Kimia Berbasis Android Menggunakan App Inventor untuk Mendukung Hasil Belajar Siswa pada Materi Asam Basa - Yenni Kurniawati; Rama Al Azmi Zega; Muhammad Safuan; Iswanda Iswanda (Entalpi Pendidikan Kimia, 2026)
Android-based learning media requires an effectiveness evaluation to assess the application of materials in schools. This study aims to evaluate the effectiveness of using Android-based Acidbase.apk chemistry learning media on acid and base materials on the learning outcomes of grade XI students at SMA Negeri 2 Bangko, compared to conventional learning methods applied at the school. This study used a Quasi Experiment design with pretest-posttest control group, and purposive sampling technique. Data were collected through student learning outcomes test. Data analysis was conducted with t-test and N-gain test. The calculation results show the tcount value (0.762) < ttable (1.995) and the significance value of 0.448 > α (0.05), so Ho is accepted and Ha is rejected. Based on the N-gain test, Android learning media is included in the low criteria with a normalised gain index of 0.28, while conventional learning is in the medium criteria with a normalised gain index of 0.44. Thus, the increase in learning outcomes using Android-based learning media is lower than the conventional method. In conclusion, computer-based applications or Android are not always effective in supporting learning outcomes. It is necessary to enrich the material on Android-based media, equipped with examples and questions, to help improve student learning outcomes to be more optimal.